Answer:
20%
Step-by-step explanation:
-6x+y=8
5x+y=8
using elimination method
Answer:
x=0, y=8. (0, 8).
Step-by-step explanation:
-6x+y=8
5x+y=8
-----------
-6x+y=8
-(5x+y)=-8
--------------
-6x+y=8
-5x-y=-8
-------------
-11x=0
x=0/-11
x=0
5(0)+y=8
0+y=8
y=8-0
y=8
(2x + 6y = -28
(x+3y=-14
YOU
how do u solve this
Answer:
Infinite Solution
Step-by-step explanation:
Your teacher gave you a tricky one lol
NVM it's right, I doubled checked
Answer:
Step-by-step explanation:
Why Do Airlines Think They Show the Best Movies?
On a separate sheet of paper write the number-letter pair next to each word that correctly names each
figure and state which property supports your answer. (use the properties given to you in the PDF notes
To solve the rhyme, rhyme. write the letter in the matching numbered box at the bottom of the
page. Provide the answer to this rhyme with your work.
Answer:
1. Rhombus
2. Square
Step-by-step explanation:
1. A rhombus is a quadrilateral whose four sides all have the same length and opposite sides are parallel.
From the diagram, you can see that [tex]\overline{AB}\parallel \overline{CD},\ \overline{AD}\parallel \overline{BC}[/tex] (given) and all four sides are congruent, thus this shape is a rhombus.
2. A square is a quadrilateral which has four equal sides, four equal angles (90-degree angles) and opposite sides are parallel.
From the diagram, you can see that [tex]\overline{EF}\parallel \overline{GH},\ \overline{EH}\parallel \overline{FG}[/tex] (given), all four sides are congruent, and all four angles are right angles, thus this shape is a square.
Find the inverse of f(x) = 3x - 2.
A) f^-1(x) = x+2/3
B) f^-1(x) = x-2/3
C) f^-1(x) = x - 2/3
D) f^-1(x) = x + 2/3
Answer:
x=0.6
Step-by-step explanation:
f(×)=3x-2 , 0=3x-2
Graph y= –3x+4 k12
im practing for a test can i get this in picture form
Figure represented the line y = -3x+4
Step-by-step explanation:
Given y=-3x+4 is equation of line
In order to graph the line, we need atleast two points
Now, When x = 0, y=?
y = -3x+4
y = -3(0) +4
y = 4
Point we get A(0,4)
Now, When x = 1, y=?
y = -3x+4
y = -3(1)+4
y = -3+4 = 1
Point we get B(1,1)
On graph, Locate points A(0,4) and B(1,1)
Draw a line passing through both of the points at once.
Figure is shown for your reference.
The sum of an irrational number and a rational number is?
Answer:
Irrational Number
Step-by-step explanation:
Which fraction is proportional to 2/5?
5/2
6/15
4/7
6/8
Answer:
6/15
Step-by-step explanation:
Because if you multiply top and bottom by 3 you get 6/15
2/5*3/3=6/15
Write -0.048 as a fraction In simplest form
Answer:
-6/125
Step-by-step explanation:
well first, the decimal is negative so automatically whatever fraction you write is going to be negative
the you look at the decimal:
-0.048
there is a 0 in the tenths place, a 4 in the hundredths place, and an 8 in the thousandths place
so that means, the fraction would be -48/1000
but since it isnt simplified, that what you have to do
both can be divided by 2
which will give you:
-24/500
but those can be divided by 2 again:
-12/250
these can also be divided by 2 again:
-6/125
since the 125 cannot be divided into 2 evenly again, this is the fraction in simplest form
The simplest form of -0.048 is -6/125.
Use the concept of fraction defined as:
A fraction is a part of the whole number and a way to split up a number into equal parts. Or, A number which is expressed as a quotient is called a fraction. It can be written in the form of p: q, which is equivalent to p / q.
The given decimal number is -0.048
Since there are 3 numbers after decimal,
Therefore,
In fractional the the number can be written as,
-0.048 = -48/1000
Divide both numerator and denominator by 8,
-0.048 = -6/125
Hence,
The simplest form of -0.048 is -6/125.
To learn more about the fraction visit:
https://brainly.com/question/5454147
#SPJ6
[hg](x,) if g(x)=x-5 and h(x)=|x|
It looks like you want to multiply the two functions. If so, then,
(h*g)(x) = h(x)*g(x)
(h*g)(x) = (x-5)*|x|
(h*g)(x) = x|x| - 5|x|
2(4x - 5) - (x - 4) solve please
Answer:
7x-6
Step-by-step explanation:
2(4x-5)-(x-4)
8x-10-x-(-4)
8x-10-x+4
7x-10+4
7x-6
Step-by-step explanation:
2(4x-5) - (x-4)
8x-10 - (x-4)
8x-10 -x+4
7x-6
The price of a pair of shoes is $52. This price is 15% lower than last week.
What was the price of the shoes last week?
Round your answer to the nearest cent.
Enter your answer in the box.
Answer:
60
Step-by-step explanation:
Answer:
$61.18
Step-by-step explanation: the first one is wrong it is $61.18
Colin and Brian were playing darts. Colin scored 62. Brian scored 59 more than Colin. What was their combined score?
Answer:
183
Step-by-step explanation:
Add 62 and 59 to get Brians score and then add another 62 to find the combined score.
Their combined score is 183.
To find the combined score of Colin and Brian, we need to add their individual scores.
Given:
- Colin's score: 62
- Brian's score: 59 more than Colin's score
We'll find Brian's score first, then add it to Colin's score to get the combined score.
Brian's score = Colin's score + 59
[tex]\[ \text{Brian's score} = 62 + 59 \][/tex]
[tex]\[ \text{Brian's score} = 121 \][/tex]
Now, to find the combined score:
[tex]\[ \text{Combined score} = \text{Colin's score} + \text{Brian's score} \][/tex]
[tex]\[ \text{Combined score} = 62 + 121 \][/tex]
[tex]\[ \text{Combined score} = 183 \][/tex]
So, their combined score is 183.
Please answer ASAP!
The sum of three numbers is -44.84. One of the numbers is 24.6. The other numbers are equal to each other. What is the value of each of the other two numbers?
Answer:
-34.72
Step-by-step explanation:
a + b + c = -44.84
a= 24.6
24.6 + b + c = -44.84
Since b = c (given "the other numbers are equal to each other")
Substitute b into c, we have
24.6 + b + b = -44.84 (b+b is the equivalence of 2 x b)
24.6 + 2b = -44.84 (subtract 24.6 from both sides)
2b = -69.44 (divide 2 from both sides)
b= -34.72
Since b = c (given "the other numbers are equal to each other")
c is also -34.72
Alison saves $29.26 each month. How many months will it take her to save enough money to buy a stereo for $339.12?
A. 10
B. 11
C. 12
D. 13
Answer:
C. 12 months
Step-by-step explanation:
If you do 339.12/29.26 it will equal to 11.589 so that's like 11 months and a half so can't be 11 months has to be 12 months
math! About 3 percent of Earth's water
is fresh water. Of that 3 percent, about
69 percent is ice. About what percent of
Earth's total water supply is ice?
Help
Answer:
2.07%
Step-by-step explanation:
69 percent of 3 percent = 0.0207 = 2.07%
Answer:2.07%
Step-by-step explanation:
Consider U = {x|x is a positive integer greater than 1}.
Which is an empty set?
{x|x ∈ U andOne-half is prime}
{x|x ∈ U and 2x is prime}
{x|x ∈ U andOne-half can be written as a fraction}
{x|x ∈ U and 2x can be written as a fraction}
Answer:
It's B
Step-by-step explanation:
I just took the test and got it right. :D
Using the definition of an empty set, we can see that the empty set in the options is:
{x|x ∈ U and 2x is prime}
Which is an empty set?
First, we know that:
U = {x|x is a positive integer greater than 1}.
So we can write:
U = {2, 3, ...}
Now, take in mind that if:
x ∈ U
Then x is a natural number larger than 1.
Now, if we multiply a natural number different than 1 by 2, we get:
2x
because x is a natural number larger than 1, 2x can't be a prime number (because it is divisible by 2 and by x).
Then the set that is empty is:
{x|x ∈ U and 2x is prime}
Because there is no element x in U that meets the condition that 2x must be prime.
If you want to learn more about empty sets:
https://brainly.com/question/14691345
#SPJ2
What is the 7th term in the geometric sequence described by this explicit formula? An=7•3(n-1)
A.15,309
B.823,543
C.729
D.5103
The 7th term of the geometric sequence described by this explicit formula [tex]a_{n}=7*3^{(n-1)}[/tex] is 5103 ⇒ answer D
Step-by-step explanation:
The explicit formula of nth term in the geometric sequence is
[tex]a_{n}=a(r)^{n-1}[/tex] , where
a is the first termr is the common ratio between each two consecutive terms∵ The explicit formula of a geometric sequence is [tex]a_{n}=7*3^{(n-1)}[/tex]
∵ The explicit formula of nth term in the geometric sequence
is [tex]a_{n}=a(r)^{n-1}[/tex]
∴ a = 7 and r = 3
∵ We need to find the 7th term
∴ n = 7
- Substitute n by 7 in the formula
∴ [tex]a_{7}=7*3^{(7-1)}[/tex]
∴ [tex]a_{7}=7*3^{(6)}[/tex]
∵ [tex]3^{(6)}=729[/tex]
∴ [tex]a_{7}=7(729)[/tex]
∴ [tex]a_{7}=5103[/tex]
The 7th term of the geometric sequence described by this explicit formula [tex]a_{n}=7*3^{(n-1)}[/tex] is 5103
Learn more:
You can learn more about geometric sequence in brainly.com/question/1522572
#LearnwithBrainly
142.5 divided by 9.5
Answer:
The answer to your question is 15
Answer: the answer is 15
Hope this helps :)
What is 10 1/2 ÷ 2 1/4
Answer:
4.66666666667 or 4[tex]\frac{2}{3}[/tex]
Step-by-step explanation:
Answer:
It would be 4 2/3.
Step-by-step explanation:
what is the multiplicative inverse of -5 1/2
Answer:
-2/11
Step-by-step explanation:
-5 1/2=-11/2
-2/11
A school drama club has 40 members. Of those students, 35% are seventh graders. How many drama club members are seventh graders?
The percentage is calculated by dividing the required value by the total value and multiplying by 100.
Required percentage value = a
total value = b
Percentage = a/b x 100
The number of members in the drama club that are seventh graders is 14.
What is a percentage?The percentage is calculated by dividing the required value by the total value and multiplying by 100.
Example:
Required percentage value = a
total value = b
Percentage = a/b x 100
Example:
50% = 50/100 = 1/2
25% = 25/100 = 1/4
20% = 20/100 = 1/5
10% = 10/100 = 1/10
5% = 5/100 = 1/20
We have,
Total number of members = 40
Percentage of members who is 7th graders = 35%
The number of 7th graders.
= 35% of 40
= 35/100 x 40
= 35/10 x 4
= 7 x 2
= 14
Thus,
The number of members in the drama club that are seventh graders is 14.
Learn more about percentages here:
https://brainly.com/question/11403063
#SPJ2
PLEASE HELP I WILL GIVE BRAINLIEST!!
Answer:
Not the commutative property but the fact that absolute value is always positive so the absolute value of x is equal to the absolute value of negative x
Step-by-step explanation:
What is the value of k in the equation 10k-7=7k-15
Answer:
k=-8/3
Step-by-step explanation:
10k-7=7k-15
10k-7k-7=-15
3k-7=-15
3k=-15+7
3k=-8
k=-8/3
Mrs. Wadley is tie-dying t-shirts for her AP Stats class. White shirts cost $4 each and black shirts are $5 each. There are 18 students in the class, and she spent $75. How many white shirts did she buy ? how many black shirts?
Mrs. Wadley bought 15 white shirts and 3 black shirts.
Step-by-step explanation:
Cost of one white shirt = $4
Cost of one black shirt = $5
Students in class = 18
Money spent on shirts = $75
Let,
white shirts = x
black shirts = y
According to given statement;
x+y=18 Eqn 1
4x+5y=75 Eqn 2
Multiplying Eqn 1 by 5;
[tex]5(x+y=18)\\5x+5y=90\ \ \ \ Eqn\ 3[/tex]
Subtracting Eqn 2 from Eqn 3;
[tex](5x+5y)-(4x+5y)=90-75\\5x+5y-4x-5y=15\\x=15[/tex]
Putting x=4 in Eqn 1
[tex]15+y=18\\y=18-15\\y=3[/tex]
Mrs. Wadley bought 15 white shirts and 3 black shirts.
Keywords: linear equation, subtraction
Learn more about linear equations at:
brainly.com/question/5341416brainly.com/question/5340976#LearnwithBrainly
Help me solve this intermediate algebra problem
Answer:
x + 1 + 4√(x-3)
Step-by-step explanation:
Given: [tex]$ (\sqrt{x - 3} + 2)^2 $[/tex]
We know that: (a + b)² = a² + b² + 2ab
Using this formula, we expand the given expression:
⇒ [tex]$ (\sqrt{x - 3} + 2)^2 = (\sqrt{x - 3})^2 + 2.\sqrt{x - 3}. 2 + 2^2 $[/tex]
⇒ [tex]$ x - 3 +4\sqrt{x - 3} + 4 $[/tex]
⇒ [tex]$ (\sqrt{x - 3} + 2)^2 $[/tex] = x + 1 +4√(x - 3).
4x + 9y = 4
9x+4y = 13
5
The tables of ordered pairs represent some points on the graphs of lines q and v.
Line 9
Line v
-9,6-
3
2
| 24410
T 1o| 8
10
| 3
y
0
18
33
Which system of equations is represented by lines q and V?
F
H
21x - y = 9
5x + 6y = 40
21x - y = 9
5x + 6y = 20
G
3x - y =-27
x + 2y = 16
9x - y = -27
x + 2y = 8
Answer:
x=101/65, y=-16/65. (101/65, -16/65).
Step-by-step explanation:
4x+9y=4
9x+4y=13
----------------
9(4x+9y)=9(4)
-4(9x+4y)=-4(13)
------------------------
36x+81y=36
-36x-16y=-52
----------------------
65y=-16
y=-16/65
4x+9(-16/65)=4
4x-144/65=4
4x=4+144/65
4x=404/65
x=(404/65)/4=101/65
x=101/65, y=-16/65.
A water park charges a rental fee plus $1.50 per hour to rent inflatable rafts. The total cost to rent a raft for 6 hours is $15. Assume the relationship is linear. Find and interpret the rate of change and the initial value.
Answer:
C = 6 + 1.5h.
$6 is the fixed fee that the park charges.
And $1.5 is the rate of charge per hour for rent of the raft.
Step-by-step explanation:
The water park charges a rental fee plus $1.5 per hour to rent inflatable rafts.
Let the total charge (C) has a linear relationship with the number of hours (h) spent in the park and it is C = a + bh ......... (1)
Now, b is the rate of charge to rent inflatable rafts and b = $1.5 per hour.
So, C = a + 1.5h ........... (2)
Now, given that the total cost to rent a raft for 6 hours is $15.
So, from equation (2) we get,
15 = a + 1.5 × 6
⇒ a = 6
Therefore, the equation (2) becomes C = 6 + 1.5h.
Here, $6 is the fixed fee that the park charges.
And $1.5 is the rate of charge per hour for rent of the raft. (Answer)
If (x – 2k) is a factor of f(x), which of the following must be true? f(2k) = 0 f(-2k) = 0 A root of f(x) is x = -2k. Ay intercept of f(x) is x = 2k.
Answer:
A. f(2k)=0
Step-by-step explanation:
The factor theorem states that a polynomial f(x) has a factor (x−k) if and only if f(k)=0 (i.e. k is a root).
If (x – 2k) is a factor of f(x), then by the factor theorem f(2k)=0 (i.e. 2k is a root).
Option A is true, f(2k)=0
Option B is false, it should be like in option A, f(2k)=0
Option C is false, because x=2k is a root, not x=-2k
Option D is false, because x-intercept of f(x) is x=2k, not y-intercept.
Answer:
A. f(2k) = 0
Step-by-step explanation:
Solve -9 (t -2) = 4(+ -15
The solution t =
Answer:
8.67
Step-by-step explanation:
-9t+18= -60
60+18=9t
78=9t
t= 78/9
=8.66
carol is excited to get a new kitten from the animal shelter. the kitten had an $299 adoption fee. carol had $50 off coupon for the adoption and will also have to pay $20 per month for food and supplies. how longg will it take for carol to spend $250
Answer:
1 month
Step-by-step explanation:
249 is the amount she spends for buying the kitten, (299-50=249) which she only has to pay once.
20 is the amount she has to spend every month, the rate of change.
The problem can be modeled with the general equation:
y = 20x + 249
In this equation, x the the time in months and y is the amount of money spent.
Substitute 250 for y.
y = 20x + 249
250 = 20x + 249 <= isolate x to get the number of months
1 = 20x
x = 1/20
Carol will only spent money every month, not for 1/20 of a month.
It will only take Carol 1 month to spent $250.
Check answer:
Substitute x for 1
y = 20x + 249
y = 20(1) + 249
y = 269
269 is more than 250 already.
Hey! How are you? My name is Maria, 19 years old. Yesterday broke up with a guy, looking for casual sex.
Write me here and I will give you my phone number - *pofsex.com*
My nickname - Lovely